Anchor system for installation of fishing gears on soft grounds - Yury V. Eremin; Dmitry B. Burlakov; Natalia N. Burlakova; Michael A. Mizyurkin; Oleg N. Kruchinin (Известия ТИНРО, 2014)
Mushroom anchors are proposed for positioning of vessels and fishing gears on soft grounds, as sands and silts. Designs of the anchors of original shape are presented. Their holding force is determined for certain navigational conditions, and the forces acting on a floating object are calculated for the cases of anchoring perpendicular and parallel to the water flow. Weight of the mushroom anchors necessary for anchoring of a floating object is calculated and scheme of the anchorage is presented for the depth 250 m. The mushroom anchors using for rescue operations in the Okhotsk Sea and for shrimp pot fishery in the Japan Sea is discussed, in particular the episode of positioning the vessel of deadweight 2433 t in conditions of 3-points roughness and the current velocity 2 knots at the sea surface and 4 knots at the sea bottom with using two stern and one bow mushroom anchors. Using of the compact mushroom anchor for shrimp pot fishery allows to reduce the traps moving along the bottom during their hauling. Possibly, the mushroom anchors could be used for other gears installation, as well, as stationary nets, crab traps, bottom longlines, etc.